1994
DOI: 10.1080/02640419408732192
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the cohesion‐performance relationship in university hockey teams

Abstract: The objective of this study was to assess, using the Group Environment Questionnaire, whether team cohesion in university-level field hockey was a cause for, or an effect of, successful performance. A quasi-experimental longitudinal design with cross-lagged correlational analysis was adopted and measures of cohesion and performance were taken midway and later in the season. The results of the synchronous correlations showed a positive relationship (with good stationarity) between team cohesion and performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
(44 reference statements)
0
12
1
Order By: Relevance
“…Some studies have addressed the connection between cohesion and performance in a variety of interactive sports. Slater and Sewell (1994), for example, measured team cohesion in hockey teams at different points of the season. They concluded that cohesiveness and success were mutually dependent and that the cohesion-performance relationship should be examined by means of a circular model in which cohesion and performance are interdependent.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Some studies have addressed the connection between cohesion and performance in a variety of interactive sports. Slater and Sewell (1994), for example, measured team cohesion in hockey teams at different points of the season. They concluded that cohesiveness and success were mutually dependent and that the cohesion-performance relationship should be examined by means of a circular model in which cohesion and performance are interdependent.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Cohesion and performance are interlinked as discovered by several researchers -Carron et al [31] found that there is "a significant circular relationship between cohesion and performance". Others such as Slater and Sewell [32] and Gould, Guinan, Greenleaf [33] concluded the presence of same "circular relationship between cohesion and performance".…”
Section: Cohesionmentioning
confidence: 97%
“…synchronous, reversed or unrelated), we first used correlation analysis (Slater and Sewell 1994). Pearson correlation coefficients were computed for the pairs of variables Su-e/ ATG-T, Su-e/GI-T and ATG-T/GI-T. To go beyond a global characteristic of the relationships between Su-e, ATG-T and GI-T and to focalise on the relational patterns that shape Su-e and each task-cohesion time series data, we explored the temporal stability of the specific relationships that organise Su-e and ATG-T on one hand, and Su-e and GI-T on the other hand.…”
Section: Identifying the Relationships Between Time Seriesmentioning
confidence: 99%